2010
DOI: 10.1007/s11892-010-0164-9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea and Diabetes: Insights into the Emerging Epidemic

Abstract: The rampant diabetes pandemic over the last few decades has been associated with an increased rise in cardiovascular events and deaths. Risk factors such as obesity, family history of diabetes, decreased physical activity, and aging are among the most common in the development of diabetes. Emerging evidence in the last 10 years has suggested that sleep apnea is a novel risk factor in the development of diabetes. Associations between diabetes and sleep apnea are supported by both epidemiologic and clinical slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Among sleep disorders, sleep-related breathing disorders, such as central sleep apnea syndrome, obstructive sleep apnea (OSA) syndrome, and sleep-related hypoventilation and hypoxemia syndrome are novel risk factors for the development of DM [8]. 1389 Associations between DM and sleep apnea were supported by both epidemiologic surveys and laboratory studies [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Among sleep disorders, sleep-related breathing disorders, such as central sleep apnea syndrome, obstructive sleep apnea (OSA) syndrome, and sleep-related hypoventilation and hypoxemia syndrome are novel risk factors for the development of DM [8]. 1389 Associations between DM and sleep apnea were supported by both epidemiologic surveys and laboratory studies [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This noninvasive treatment operates by ventilating air through the mouth and nose during sleep, thereby decreasing sleep fragmentations and other sleep abnormalities. 5 Utilizing CPAP intervention on a regular basis results in enhanced maintenance of normal glucose levels, improved insulin sensitivity, and better maintenance of appropriate leptin and ghrelin hormone levels. 5,12 Previous research has demonstrated that those diagnosed both with diabetes and an SD who were complaining of fatigue and excessive daytime sleepiness were prescribed a CPAP for several months.…”
Section: Managing Diabetes and Sleep Disordersmentioning
confidence: 99%
“…5,6 Although diabetes management is improving, complications are still common, and diabetes remains the leading cause of visual loss, amputation, and end stage of renal disease in the United States. 2,5,6 Similar to diabetes, sleep disturbances are related to myriad health problems, affecting approximately 70 million Americans. 1 The extent to which sleep disorders (SDs) affect overall health and functionality has not been clearly ascertained because significant inadequate diagnoses and underdiagnoses of SDs; an estimated 85% of SDs go undiagnosed or untreated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The far-reaching effects of sleep disorders and deprivation underscore the need for evaluation and treatment of sleep problems in patients with various psychiatric conditions.…”
mentioning
confidence: 99%